(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the phytomass and productivity of the watermelon according to the number of fruits per plant and the planting spacing. The experimental design used was in randomized blocks with four replications and the treatments were allocated in subdivided plots of type 2 x 4. The plot consisted of the number of fruits per plant (1 and 2 fruits) and in the subplot by the planting spacing (3, 0 x 0.4 m), (3.0 x 0.8 m), (3.0 x 1.2 m) and (3.0 x 1.6 m). The cultivation of the watermelon in the denser spacing of 3.0 x 0.4 m associated with the conduction of plants with two fruits stood out significantly in the accumulation of total dry mass in the plant. The denser spacing associated with the plant’s conduction with only one fruit raised the average fruit mass of the watermelon. The conduction of the plant with two fruits and in the spacing of 3.0 x 0.4 m registered the highest productivity of the culture.